Guanxi networks as business and investment advantage of Overseas Chinese in Mainland China - Rottwinkel, Tobias (2012)
Guanxi has been a fundamental element of the Chinese culture for centuries and its significance in modern day China should not be underestimated. Guanxi is considered to be an essential means for business and corporate success in China. It can inter alia facilitate the access to top-level decision-makers, reduce information and transaction costs, and improve the overall competitive positioning of a firm. The dissertation aims to analyse guanxi in the context of ethnical Chinese investment in China. It is analysed whether guanxi constitutes a unique investment advantage that ethnical Chinese possess over Western companies. A case study analysis of Robert Kuok’s business operations provides practical insight into the benefits of guanxi and its implications for Western companies using the example of Coca Cola in China.